(untitled) (World of finance, 2023)
Introduction. The combination of financial, material, and informational resources in the digital economy for the provision of high-quality municipal services led to the formation of smart cities. Smart city is the newest stage of development of social formations within the framework of territorial associations of residents, the infrastructural basis of which is the transport system. The functioning of passenger carriers and the management of their financial activities based on accounting information in the smart city undergoes significant transformations that require detailed research. It has determined the relevance of the research topic and its purpose. The purpose of the article is to determine the impact on the financial results of the use of the latest information and communication technologies in the transport sector to optimize the management of passenger flows and the financial and economic activities of passenger carriers in the smart city. Results. Seven main trends in the development of passenger transport in the context of a smart city have been identified and systematized: integration, greening, digitization of fare payment, commodification of transportation, autonomy and safety, electrification, spatial movement of vehicles. The influence of innovative directions of transport development of smart cities on the financial results of the operation of passenger carriers is studied. A fundamental scheme of the information environment of passenger transportation has been developed, which includes: elements of the transport system; participants in the passenger transportation market; information and communication technologies in the transport sector, which are used by passenger carriers in the smart city; the information system of transport enterprises, the basic element of which is an integrated accounting database; management system of business entities in the transport sector of the economy. The expediency of the transformation of the passenger transport management system of the smart city information environment, which provides for autonomous self-regulation of transport and passenger flows and digitization of financial and economic management based on accounting information, is substantiated. Conclusions. The implementation of the author’s proposals and developments ensures effective management of passenger flows for the implementation of passenger needs in the smart city and management of the financial and economic activities of carriers in order to obtain profit from the provision of transport service s. The transformation of the methodology and organization of accounting for the functioning of passenger carriers using the latest information and communication technologies in the smart city requires a more detailed research in the future scientific works.